Use of laboratory test results in patient management by clinicians in Malawi - Kundai Moyo; Carol Porter; Ben Chilima; Reuben Mwenda; Mark Kabue; Lutho Zungu; Abdoulaye Sarr (AOSIS, 2015)
Background: Malawi has a high burden of infectious disease. The expansion of programmes targeting these diseases requires a strong laboratory infrastructure to support both diagnosis and treatment.Objectives: To assess the use of laboratory test results in patient management and to determine the requirements for improving laboratory services. Methods: A cross-sectional study was conducted in 2012 to survey practising clinicians.Two hospitals were purposively selected for observations of clinicians ordering laboratory tests. Twelve management-level key informants were interviewed. Descriptive statistics were conducted. Results: A total of 242 clinicians were identified and 216 (89%) were interviewed. Of these, 189 (87%) reported doubting laboratory test results at some point. Clinicians most often doubted the quality of haematology (67%), followed by malaria (53%) and CD4 (22%) test results. A total of 151 (70%) clinicians reported using laboratory tests results in patient management. Use of laboratory test results at all times in patient management varied by the type of health facility (P < 0.001). Ninety-one percent of clinicians reported that laboratories required infrastructure improvement. During 97 observations of clinicians' use of laboratory test results, 80 tests were ordered, and 73 (91%) of these were used in patient management. Key informants reported that the quality of laboratory services was good and useful, but that services were often unavailable. Conclusion: Gaps in the public laboratory system were evident. Key recommendations to enhance the use of laboratory test results in patient management were to strengthen the supply chain, reduce turn-around times, improve the test menu and improve the laboratory infrastructure.